Nitrogen-doped reduced graphene oxide for high efficient adsorption of methylene blue - Maoping Kang; Yongli Pei; Ying Zhang; Lihong Su; Yuxiang Li; Hongyu Wang (Frontiers in Chemistry)
A highly efficient and widely applicable adsorbent for the removal of methylene blue (MB) was created using nitrogen-doped and reduced graphene oxide (NRGO). The effects of NRGO mass, pH, contact time, and the initial MB concentration on the adsorption properties of MB onto NRGO were investigated. The results showed that the adsorption behavior remained stable within the pH range of 2.0–10.0, and the adsorption process gradually reached equilibrium after 24 h. Additionally, the adsorption kinetics and adsorption isotherms were discussed to propose a theoretical adsorption mechanism. Meanwhile, some characterizations including Scanning Electron Microscopy, Energy Disperse X-ray Spectroscopy, X-ray Photoelectron Spectroscopy, X-ray Powder Diffraction, Fourier Transform Infrared Spectroscopy, etc. were used to explore potential adsorption mechanism, which indicated the physisorption caused by π-π bonds was the main adsorption mechanism. NRGO exhibits efficient MB absorption and holds significant potential application for the wastewater treatment.